Delayed participation of developing countries to climate agreements: should action in the EU and US be postponed? - Valentina Bosetti; Carlo Carraro; Massimo Tavoni (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyses the cost implications for climate policy in developed countries if developing countries are unwilling to adopt measures to reduce their own GHG emissions. First, we assume that a 450 CO2 (550 CO2e) ppmv stabilisation target is to be achieved and that Non Annex1 (NA1) countries decide to delay their GHG emission reductions by 30 years. What would be the cost difference between this scenario and a case in which both developed and developing countries start reducing their emissions at the same time? Then, we look at a scenario in which the timing of developing countries' participation is uncertain and again we compute the costs of climate policy in developed and developing countries. We find that delayed participation of NA1 countries has a negative impact on climate policy costs. Economic inefficiencies can be as large as 10-25 TlnUSD. However, this additional cost wanes when developing countries are allowed to trade emission reductions from their baseline emission paths during the 30-year delay period. Thus, irrespective of whether NA1 countries are immediately assigned an emission reduction target or not, they should nonetheless be included in a global carbon market. Technology deployment is also affected by the timing of developing countries' mitigation measures. Delayed NA1-country participation in a climate agreement would scale down the deployment of coal with CCS throughout the century. On the other hand, innovation in the form of energy R&D investments would be positively affected, since it would become crucial in developed countries. Finally, uncertainty about the timing of NA1-country participation does not modify the optimal abatement strategy for developed countries and does not alter policy costs as long as a global carbon market is in place. - Delayed action ; climate policy ; stabilisation costs ; uncertain participation
Keywords: C72; H23; Q25; Q28; 330; Klimaveränderung; Treibhausgas; Kohlendioxid; Umweltschutzkosten; Umweltpolitik; Umweltabkommen; Mitgliedschaft; Entwicklungsländer; Welt